Pembangunan Ekonomi Lokal Dalam Perspektif Teori Tahap Pembangunan Kecamatan Paiton - Junaedi, Deddy; Subairiyah, Nikmatus; Fitri W, Noviana Fitri W; Lutfia, Sinta (Jurnal Ekonomi dan Bisnis Digital, 2026)
Local economic development is a vital strategy for fostering growth and ensuring the equitable distribution of community welfare at the regional level. As a strategic area in the Probolinggo Regency, Paiton District possesses diverse economic potential across the industrial, agricultural, trade, and service sectors. Nevertheless, the utilization of this potential is still hindered by various socio-economic barriers. This study aims to analyze local economic development in Paiton District through the perspective of Development Stage Theory, specifically to identify the position and characteristics of the economic development stages currently experienced by the region. The research methodology employed is a qualitative study with a descriptive-analytical approach, utilizing data collection techniques such as in-depth interviews, field observations, and documentation. The results indicate that local economic development in Paiton District is in a transitional phase, moving from a traditional economy toward a more modern growth stage. This is characterized by the expansion of the industrial sector and non-agricultural economic activities; however, the region still faces challenges regarding human resource limitations, inequality in economic access, and the suboptimal role of local institutions. Consequently, a more integrated local economic development strategy based on regional potential is required to accelerate the process of sustainable development.